PO227 A clinical trial of telehealth to improve timely access to specialist care. (1st December 2017) - Hobson, Esther; Bradburn, Mike; Baird, Wendy; Cooper, Cindy; Mawson, Sue; Quinn, Ann; Shaw, Pamela; Walsh, Theresa; McDermott, Christopher
Abstract : Specialist multidisciplinary care is associated with increased survival. We developed a telehealth system to improve access to specialist care and reduce the burden of travel to specialist centres. We explored the feasibility of telehealth and the feasibility in a motor neurone disease population covering a large geographical area. 40 patients plus 37 informal carers were randomised to usual care or telehealth plus usual care. Interviews explored participants' and clinicians' experiences of MND care and the telehealth system. We also collected data on telehealth use, clinical outcomes and quality of life. The telehealth system was reported to be easy to use, even by patients with severe disability or no technology experience. Patients reported that the service provided reassurance and knowledge of MND and could improve communication and problem solving. Challenges included how to make the service interactive and meet the expectations of patients, carers and staff. However, telehealth appeared to be an acceptable alternative or addition to clinic appointments, particularly in early disease or for patients unable to travel. We have developed telehealth service that could be feasible and acceptable. We have also developed an understanding of how novel methods of neurology care delivery could reduce service costs and patient burden. We have developed a feasible and acceptable telehealth service and an understanding of how novel methods of service delivery could be successful.